Managing Internal Communication for Employee Engagement Towards Customer Satisfaction: A Case Study of a Thai Restaurant Chain - Serirungsun, panet (Creative Business and Sustainability Journal, 2018)
Abstract This qualitative research investigates how employee engagement towards customer satisfaction can be driven through internal communication at a Thai restaurant chain. The study delves into mechanisms the company uses to internally communicate customer-centered issues to its members, how internal communication brings customer-focused employee engagement to the firm, and the approaches to overcome potential barriers to internal communication. Data collecting methods mainly consist of in-depth interviews with five top executives and four focus-group discussions with five employees in each group. With qualitative data analysis, results show that the indispensable off-line communication formats include the highest-ranking executive’s being good role model of customer-satisfaction enthusiast, training center, mobile teaching, and informal face-to-face meeting while e-mail and Line application are on-line channels particularly working for management-level employees. To drive employee engagement in customer-centered activities and overcome internal communication barriers, the firm exploits communication mechanisms and tactics, including implementing Kaizen projects and Im-Jai group meetings as two-way communication, delivering clear and easy-to-understand messages to employees, and making contents truly audience-oriented by applying the WIIFM concept. The communication framework proposed in this study suggests research potentials for communication and organization disciplines and can be used as a guideline by corporate communicators for designing internal communication strategies to drive employee engagement in any business-related concerns.